2008
DOI: 10.1098/rspb.2008.0105
|View full text |Cite
|
Sign up to set email alerts
|

You are what your mother eats: evidence for maternal preconception diet influencing foetal sex in humans

Abstract: Facultative adjustment of sex ratios by mothers occurs in some animals, and has been linked to resource availability. In mammals, the search for consistent patterns is complicated by variations in mating systems, social hierarchies and litter sizes. Humans have low fecundity, high maternal investment and a potentially high differential between the numbers of offspring produced by sons and daughters: these conditions should favour the evolution of facultative sex ratio variation. Yet little is known of natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(117 citation statements)
references
References 54 publications
7
108
2
Order By: Relevance
“…Previous research has also specifically linked environmental exposures around the time of conception to fewer male births either because fewer males are conceived or because fewer male embryos survive (e.g., Hansen, Mǿller, and Olsen 1999). In a provocative study, Mathews, Johnson, and Neil (2008) find that poor nutrition around the time of conception results in fewer male births and suggest that breakfast skipping could explain their findings. 3 Almond and Mazumder (2011) also find that maternal fasting around the time of conception sharply lowers the share of male births.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Previous research has also specifically linked environmental exposures around the time of conception to fewer male births either because fewer males are conceived or because fewer male embryos survive (e.g., Hansen, Mǿller, and Olsen 1999). In a provocative study, Mathews, Johnson, and Neil (2008) find that poor nutrition around the time of conception results in fewer male births and suggest that breakfast skipping could explain their findings. 3 Almond and Mazumder (2011) also find that maternal fasting around the time of conception sharply lowers the share of male births.…”
Section: Introductionmentioning
confidence: 65%
“…Provocative studies by Mathews, Johnson, and Neil (2008) and Almond and Mazumder (2011) highlight the potential role of intermittent fasting and suggest the usefulness of exploring additional sources of variation in fasting or meal skipping. The study by Mathews, Johnson, and Neil (2008) is purely observational, and it would therefore be helpful to replicate their findings using a research design that may more plausibly utilize exogenous variation in breakfast skipping. Second, their sample only utilized 740 women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latitude values, namely rounded latitude for the centroid or centre point of a country expressed in degrees and minutes, for nations were obtained from the CIA World Factbook (CIA, 2011) and numerical values were used irrespective of direction. Testing the relation of high resource availability and male-biased sex ratios frequently found in many animals, Mathews et al (2008) studied a large cohort of British Women and found that 56% of women in the highest third of preconception energy intake bore boys, compared with 45% in the lowest third. Disability-adjusted life years (DALY) lost due to protein energy malnutrition, iodine deficiency, vitamin A deficiency, and iron deficiency were used as an independent measure of nutrition stress.…”
Section: Independent Variablesmentioning
confidence: 99%
“…It is possible that other factors besides ambient temperature are influencing variation in the proportion of males born in Australia and New Zealand. For example, maternal nutritional status and, in particular, preconception energy intake was positively associated with a greater proportion of male births in a UK study (Mathews et al 2008). Further, in Helle et al's (2009) study where ambient temperature was positively associated with the SSR, periods of famine showed a negative association.…”
Section: Discussionmentioning
confidence: 88%